Solid electrolyte material and battery using the same

By adopting a solid electrolyte material with a specific composition, the problems of low lithium ion conductivity and safety of hydrogen sulfide in the prior art are solved, and a battery material with high lithium ion conductivity and safety is achieved, which is suitable for the charging and discharging characteristics of all solid batteries. optimization.

CN115769313BActive Publication Date: 2024-12-27PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202180044028.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-07-22
Filing Date
2021-06-08
Publication Date
2024-12-27
Estimated Expiration
2041-06-08

AI Technical Summary

Technical Problem

The prior art is difficult to provide solid electrolyte materials with high lithium ion conductivity, and sulfide solid electrolytes may produce hydrogen sulfide when exposed to the atmosphere, affecting safety.

Method used

A solid electrolyte material consisting of Li, M1, M2 and X is used, where M1 selects Ca, Mg, Zn, M2 selects Y, Gd, Sm, X selects F, Cl, Br, I, and is processed through specific composition ratios and processes. , form a material with high lithium ion conductivity and ensures that the material does not contain sulfur or sulfur content is extremely low.

Benefits of technology

A solid electrolyte material with high lithium ion conductivity ensures the safety and stability of the material, does not produce hydrogen sulfide in the atmosphere, and is suitable for the optimization of charge and discharge characteristics of all-solid batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115769313B_ABST
    Figure CN115769313B_ABST
Patent Text Reader

Abstract

The solid electrolyte material disclosed in the present invention is formed of Li, M1, M2 and X, wherein M1 is at least two selected from Ca, Mg and Zn, M2 is at least one selected from Y, Gd and Sm, and X is at least one selected from F, Cl, Br and I.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a solid electrolyte material and a battery using the solid electrolyte material. Background Art

[0002] Patent Document 1 discloses an all-solid-state battery using a sulfide solid electrolyte.

[0003] Patent Document 2 discloses a solid electrolyte material represented by the compositional formula Li 6-3z Y z X6 (0 < z < 2, X = Cl or Br).

[0004] Prior Art Documents

[0005] Patent Documents

[0006] Patent Document 1: Japanese Unexamined Patent Application Publication No. 2011-129312

[0007] Patent Document 2: International Publication No. 2018 / 025582 Summary of the Invention

[0008] Problems to be Solved by the Invention

[0009] An object of the present disclosure is to provide a solid electrolyte material having a high lithium ion conductivity (also referred to as lithium ion electric conductivity, lithium ion conductivity).

[0010] Means for Solving the Problems

[0011] The solid electrolyte material of the present disclosure is formed of Li, M1, M2, and X, where M1 is at least two selected from Ca, Mg, and Zn, M2 is at least one selected from Y, Gd, and Sm, and X is at least one selected from F, Cl, Br, and I.

[0012] Effects of the Invention

[0013] The present disclosure provides a solid electrolyte material having a high lithium ion conductivity. Brief Description of the Drawings

[0014] Figure 1 A cross-sectional view showing the battery 1000 of the second embodiment.

[0015] Figure 2 A schematic diagram showing a pressure molding die 300 for evaluating the ionic conductivity of a solid electrolyte material.

[0016] Figure 3 A graph showing a Cole-Cole plot obtained from the AC impedance measurement results of the solid electrolyte material of Example 1.

[0017] Figure 4 : is a figure which shows the X-ray diffraction pattern of the solid electrolyte material of Examples 1 to 18.

[0018] Figure 5 : is a figure which shows the X-ray diffraction pattern of the solid electrolyte material of Examples 19 to 37.

[0019] Figure 6 This is a graph showing the initial discharge characteristics of the battery of Example 1. DETAILED DESCRIPTION

[0020] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings.

[0021] (First embodiment)

[0022] The solid electrolyte material of the first embodiment is formed of Li, M1, M2, and X. M1 is at least two selected from Ca, Mg, and Zn. M2 is at least one selected from Y, Gd, and Sm. X is at least one selected from F, Cl, Br, and I.

[0023] The solid electrolyte material of the first embodiment has high lithium ion conductivity. Here, high lithium ion conductivity means, for example, 1 mS / cm or more at around room temperature. That is, the solid electrolyte material of the first embodiment can have, for example, ion conductivity of 1 mS / cm or more.

[0024] The solid electrolyte material of the first embodiment can be used to obtain a battery having excellent charge and discharge characteristics. An example of such a battery is an all-solid battery. The all-solid battery may be a primary battery or a secondary battery.

[0025] The solid electrolyte material of the first embodiment preferably contains substantially no sulfur. "The solid electrolyte material of the first embodiment contains substantially no sulfur" means that the solid electrolyte material does not contain sulfur as a constituent element except for sulfur that is inevitably mixed in as an impurity. In this case, the sulfur mixed in the solid electrolyte material as an impurity is, for example, less than 1 mol%. The solid electrolyte material of the first embodiment preferably contains no sulfur. The solid electrolyte material that does not contain sulfur will not produce hydrogen sulfide even if exposed to the atmosphere, and therefore has excellent safety. The sulfide solid electrolyte disclosed in Patent Document 1 can produce hydrogen sulfide if exposed to the atmosphere.

[0026] The solid electrolyte material of the first embodiment may contain an element that is inevitably mixed in. Examples of such an element are hydrogen, oxygen, or nitrogen. Such an element may exist in the raw material powder or the atmosphere of the solid electrolyte material used to produce or store the solid electrolyte material.

[0027] To improve the ionic conductivity of the solid electrolyte material, M1 can be Ca and Mg, or Ca and Zn.

[0028] To improve the ionic conductivity of the solid electrolyte material, M2 can also contain Y.

[0029] To improve the ionic conductivity of the solid electrolyte material, X can also be at least one selected from Cl and Br.

[0030] The solid electrolyte material of the first embodiment can be a material represented by the following compositional formula (1).

[0031] Li 3-2a-3b (Ca 1-x M1′ x ) a (Y 1-y M2′ y ) 1+b Br 6-z Cl z (1)

[0032] Wherein,

[0033] M1′ is at least one selected from Zn and Mg,

[0034] M2′ is at least one selected from Gd and Sm,

[0035] And the following four mathematical formulas are satisfied:

[0036] 0 < a ≤ 0.3,

[0037] 0 ≤ b ≤ 0.1,

[0038] 0 < x ≤ 0.5,

[0039] 0 ≤ y ≤ 0.9 and

[0040] 0 ≤ z ≤ 6.

[0041] The material represented by the compositional formula (1) has high ionic conductivity.

[0042] To improve the ionic conductivity of the solid electrolyte material, in the compositional formula (1), the mathematical formula: 3 ≤ z ≤ 4.5 can be satisfied.

[0043] The upper and lower limit values of the range of a in the compositional formula (1) can be defined by any combination selected from values exceeding 0 (i.e., 0 < a), 0.05, 0.1, 0.15, 0.2, and 0.3.

[0044] The upper and lower limit values of the range of b in the compositional formula (1) can be defined by any combination selected from the values 0, 0.05, and 0.1.

[0045] The upper limit value and the lower limit value of the range of x in the compositional formula (1) can be defined by any combination selected from values exceeding 0 (i.e., 0 < x), 0.1, 0.2, 0.3, and 0.5.

[0046] The upper limit value and the lower limit value of the range of y in the compositional formula (1) can be defined by any combination selected from the values 0, 0.1, 0.2, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9.

[0047] The upper limit value and the lower limit value of the range of z in the compositional formula (1) can be defined by any combination selected from the values 3, 3.5, 4, and 4.5.

[0048] The X-ray diffraction pattern of the solid electrolyte material in the first embodiment can be obtained by using Cu-Kα rays (wavelength and i.e., wavelengths 0.15405 nm and 0.15444 nm) and performing X-ray diffraction measurement using the θ-2θ method. In the obtained X-ray diffraction pattern, a first peak can exist in the range of diffraction angle 2θ of 30.0° or more and 31.0° or less, and a second peak can exist in the range of diffraction angle 2θ of 39.0° or more and 40.3° or less. Additionally, a third peak can exist in the range of diffraction angle 2θ of 15.0° or more and 15.7° or less, a fourth peak can exist in the range of diffraction angle 2θ of 16.3° or more and 17.1° or less, and a fifth peak can exist in the range of diffraction angle 2θ of 46.6° or more and 48.1° or less. The crystal phase having these peaks is referred to as the first crystal phase. The solid electrolyte material containing the first crystal phase has high ionic conductivity.

[0049] The first crystal phase belongs to the trigonal system. The "trigonal system" in the present disclosure refers to a crystal phase having a crystal structure similar to that of Li3ErCl6 disclosed in the ICSD (Inorganic Crystal Structure Database) Collection Code 50151 and having an X-ray diffraction pattern characteristic of this structure. In the present disclosure, "having a similar crystal structure" means being classified in the same space group and having a close atomic configuration structure, and does not limit the lattice constant.

[0050] The solid electrolyte material of the first embodiment may further contain a second crystal phase different from the first crystal phase. That is, the solid electrolyte material of the first embodiment may also further contain a second crystal phase having a peak outside the above range of diffraction angle 2θ. The second crystal phase may also be interposed between the first crystal phases.

[0051] The shape of the solid electrolyte material of the first embodiment is not limited. Examples of the shape are needle-shaped, spherical, or ellipsoidal. The solid electrolyte material of the first embodiment may also be particles. The solid electrolyte material of the first embodiment may also be formed in a particle or plate shape.

[0052] In the case where the shape of the solid electrolyte material of the first embodiment is, for example, a particle shape (e.g., a sphere), the solid electrolyte material may have a median diameter of 0.1 μm or more and 100 μm or less. The median diameter refers to the particle diameter when the cumulative volume in the volume-based particle size distribution is equal to 50%. The volume-based particle size distribution is measured by, for example, a laser diffraction measuring device or an image analysis device.

[0053] The solid electrolyte material of the first embodiment may have a median diameter of 0.5 μm or more and 10 μm or less. Thus, the solid electrolyte material of the first embodiment has higher ion conductivity. In addition, when the solid electrolyte material of the first embodiment is mixed with other materials such as an active material, the dispersion state of the solid electrolyte material of the first embodiment and the other materials becomes good.

[0054] <Method for producing solid electrolyte material>

[0055] The solid electrolyte material of the first embodiment is produced by, for example, the following method.

[0056] The raw material powder is prepared and mixed so as to have a target composition. The raw material powder may be, for example, a halide.

[0057] As an example, when the target composition is Li 2.6 Ca 0.18 Zn 0.02 Y 0.3 G 0.7 Br 2.5 Cl 3.5 In the case of , LiCl raw material powder, LiBr raw material powder, CaBr2 raw material powder, ZnBr2 raw material powder, YBr3 raw material powder, GdCl3 raw material powder (i.e., raw material powders of 6 halides) are mixed in a molar ratio of about LiCl: LiBr: CaBr2: ZnBr2: YBr3: GdCl3 = 1.4: 1.2: 0.18: 0.02: 0.3: 0.7. The raw material powders may also be mixed in a molar ratio pre-adjusted in a manner to offset composition changes that may occur in the synthesis step.

[0058] The mixture of raw material powders is fired in an inert gas atmosphere to react with each other to obtain a reactant. Examples of the inert gas are helium, nitrogen or argon. The firing can be performed in a vacuum. During the firing process, the mixture of raw material powders can also be placed in a container (such as a crucible and a vacuum sealed tube) and fired in a heating furnace.

[0059] Alternatively, the raw material powders may be mechanochemically reacted with each other in a mixing device such as a planetary ball mill to obtain a reactant. That is, the raw material powders may be mixed and reacted using a mechanochemical grinding method. The reactant obtained by such operation may also be further calcined in an inert gas atmosphere or in a vacuum.

[0060] By these methods, the solid electrolyte material of the first embodiment can be obtained.

[0061] (Second embodiment)

[0062] The second embodiment will be described below. Matters described in the first embodiment may be omitted as appropriate.

[0063] In the second embodiment, an electrochemical device using the solid electrolyte material of the first embodiment will be described. As the electrochemical device of the second embodiment, a battery will be described below.

[0064] The battery of the second embodiment comprises a positive electrode, a negative electrode and an electrolyte layer. The electrolyte layer is provided between the positive electrode and the negative electrode. At least one selected from the positive electrode, the electrolyte layer and the negative electrode contains the solid electrolyte material of the first embodiment.

[0065] The battery of the second embodiment has excellent charge and discharge characteristics because it contains the solid electrolyte material of the first embodiment. The battery may be an all-solid-state battery.

[0066] Figure 1 A cross-sectional view of a battery 1000 according to a second embodiment is shown.

[0067] The battery 1000 of the second embodiment includes a positive electrode 201 , an electrolyte layer 202 , and a negative electrode 203 . The electrolyte layer 202 is provided between the positive electrode 201 and the negative electrode 203 .

[0068] The positive electrode 201 includes positive electrode active material particles 204 and solid electrolyte particles 100 .

[0069] The electrolyte layer 202 contains an electrolyte material. The electrolyte material is, for example, a solid electrolyte material.

[0070] The negative electrode 203 includes negative electrode active material particles 205 and solid electrolyte particles 100 .

[0071] The solid electrolyte particle 100 is a particle formed of the solid electrolyte material of the first embodiment, or a particle containing the solid electrolyte material of the first embodiment as a main component. Here, "a particle containing the solid electrolyte material of the first embodiment as a main component" refers to a particle in which the component contained most by molar ratio is the solid electrolyte material of the first embodiment. The solid electrolyte particle 100 may also be a particle formed of the solid electrolyte material of the first embodiment.

[0072] The positive electrode 201 contains a material capable of inserting and removing metal ions (eg, lithium ions), such as a positive electrode active material (eg, positive electrode active material particles 204 ).

[0073] Examples of positive electrode active materials are lithium-containing transition metal oxides, transition metal fluorides, polyanionic materials, fluorinated polyanionic materials, transition metal sulfides, transition metal fluorides, transition metal oxysulfides or transition metal oxynitrides. Examples of lithium-containing transition metal oxides are Li(Ni,Co,Al)O2 or LiCoO2.

[0074] In the present disclosure, the symbol “(A, B, C)” in a chemical formula means “at least one selected from A, B, and C.” The same applies to other elements.

[0075] The positive electrode active material particles 204 may have a median diameter of 0.1 μm or more and 100 μm or less. When the positive electrode active material particles 204 have a median diameter of 0.1 μm or more, the dispersion state of the positive electrode active material particles 204 and the solid electrolyte particles 100 in the positive electrode 201 becomes good. As a result, the charge and discharge characteristics of the battery are improved. When the positive electrode active material particles 204 have a median diameter of 100 μm or less, the lithium diffusion rate in the positive electrode active material particles 204 is increased. As a result, the battery can operate at a high output power.

[0076] The positive electrode active material particles 204 may have a larger median diameter than the solid electrolyte particles 100. This improves the dispersion state of the positive electrode active material particles 204 and the solid electrolyte particles 100 in the positive electrode 201.

[0077] To improve the energy density and output of the battery, in the positive electrode 201 , the ratio of the volume of the positive electrode active material particles 204 to the total volume of the positive electrode active material particles 204 and the volume of the solid electrolyte particles 100 may be 0.30 or more and 0.95 or less.

[0078] In order to improve the energy density and output power of the battery, the positive electrode 201 may have a thickness of 10 μm or more and 500 μm or less.

[0079] The electrolyte layer 202 contains an electrolyte material. The electrolyte material is, for example, a solid electrolyte material. The electrolyte layer 202 may also be a solid electrolyte layer.

[0080] The electrolyte layer 202 may also contain the solid electrolyte material of the first embodiment. The electrolyte layer 202 may be composed only of the solid electrolyte material of the first embodiment. Alternatively, the electrolyte layer 202 may also be composed only of a solid electrolyte material different from the solid electrolyte material of the first embodiment.

[0081] Examples of solid electrolyte materials different from the solid electrolyte material of the first embodiment include Li2MgX'4, Li2FeX'4, Li(Al,Ga,In)X'4, Li3(Al,Ga,In)X'6, or LiI, wherein X' is at least one selected from F, Cl, Br, and I.

[0082] Hereinafter, the solid electrolyte material of the first embodiment is referred to as a first solid electrolyte material. A solid electrolyte material different from the solid electrolyte material of the first embodiment is referred to as a second solid electrolyte material.

[0083] The electrolyte layer 202 may contain not only the first solid electrolyte material but also the second solid electrolyte material. The first solid electrolyte material and the second solid electrolyte material may be uniformly dispersed in the electrolyte layer 202. The layer formed by the first solid electrolyte material and the layer formed by the second solid electrolyte material may be stacked along the stacking direction of the battery 1000.

[0084] The electrolyte layer 202 may have a thickness of 1 μm or more and 1000 μm or less. When the electrolyte layer 202 has a thickness of 1 μm or more, the positive electrode 201 and the negative electrode 203 are less likely to short-circuit. When the electrolyte layer 202 has a thickness of 1000 μm or less, the battery can operate at a high output power.

[0085] The negative electrode 203 contains a material capable of inserting and removing metal ions such as lithium ions. This material is, for example, a negative electrode active material (for example, negative electrode active material particles 205 ).

[0086] Examples of negative electrode active materials are metal materials, carbon materials, oxides, nitrides, tin compounds or silicon compounds. The metal material may be a single metal or an alloy. Examples of metal materials are lithium metal or lithium alloys. Examples of carbon materials are natural graphite, coke, graphitized carbon, carbon fiber, spherical carbon, artificial graphite or amorphous carbon. From the viewpoint of capacity density, preferred examples of negative electrode active materials are silicon (i.e., Si), tin (i.e., Sn), silicon compounds or tin compounds.

[0087] The negative electrode active material particles 205 may have a median diameter of 0.1 μm or more and 100 μm or less. When the negative electrode active material particles 205 have a median diameter of 0.1 μm or more, the dispersion state of the negative electrode active material particles 205 and the solid electrolyte particles 100 in the negative electrode 203 becomes good. As a result, the charge and discharge characteristics of the battery are improved. When the negative electrode active material particles 205 have a median diameter of 100 μm or less, the lithium diffusion rate in the negative electrode active material particles 205 is increased. As a result, the battery can operate at a high output power.

[0088] The negative electrode active material particles 205 may have a larger median diameter than the solid electrolyte particles 100. This improves the dispersion state of the negative electrode active material particles 205 and the solid electrolyte particles 100 in the negative electrode 203.

[0089] To improve the energy density and output of the battery, in the negative electrode 203 , the ratio of the volume of the negative electrode active material particles 205 to the total volume of the negative electrode active material particles 205 and the volume of the solid electrolyte particles 100 may be 0.30 or more and 0.95 or less.

[0090] In order to improve the energy density and output power of the battery, the negative electrode 203 may have a thickness of 10 μm or more and 500 μm or less.

[0091] In order to improve ion conductivity, chemical stability, and electrochemical stability, at least one selected from the positive electrode 201, the electrolyte layer 202, and the negative electrode 203 may contain a second solid electrolyte material.

[0092] As described above, the second solid electrolyte material may be a halide solid electrolyte.

[0093] Examples of halide solid electrolytes include Li2MgX'4, Li2FeX'4, Li(Al,Ga,In)X'4, Li3(Al,Ga,In)X'6 or LiI, wherein X' is at least one selected from F, Cl, Br and I.

[0094] The second solid electrolyte material may be a sulfide solid electrolyte.

[0095] Examples of sulfide solid electrolytes are Li2S-P2S5, Li2S-SiS2, Li2S-B2S3, Li2S-GeS2, Li 3.25 Ge 0.25 P 0.75 S4 or Li 10 GeP2S 12 .

[0096] The second solid electrolyte material may be an oxide solid electrolyte.

[0097] Examples of oxide solid electrolytes are:

[0098] (i) NASICON-type solid electrolytes such as LiTi2(PO4)3 or its elemental substitutions,

[0099] (ii) Perovskite-type solid electrolytes such as (LaLi)TiO3,

[0100] (iii)Li 14 ZnGe4O 16 , LISICON type solid electrolytes such as Li4SiO4, LiGeO4 or their elemental substitutions,

[0101] (iv)Li7La3Zr2O 12 or its elemental substitution such as garnet-type solid electrolyte, or

[0102] (v) Li3PO4 or its N-substituted product.

[0103] The second solid electrolyte material may be an organic polymer solid electrolyte.

[0104] Examples of organic polymer solid electrolytes include compounds of polymer compounds and lithium salts. The polymer compound may have an ethylene oxide structure. The polymer compound having an ethylene oxide structure can contain a large amount of lithium salt, thereby further improving ion conductivity.

[0105] Examples of lithium salts include LiPF6, LiBF4, LiSbF6, LiAsF6, LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9) or LiC(SO2CF3)3. One lithium salt selected from the above may be used alone. Alternatively, a mixture of two or more lithium salts selected from the above may be used.

[0106] In order to facilitate the transfer of lithium ions and thus improve the output characteristics of the battery, at least one selected from the positive electrode 201, the electrolyte layer 202, and the negative electrode 203 may contain a non-aqueous electrolyte, a gel electrolyte, or an ionic liquid.

[0107] The non-aqueous electrolyte contains a non-aqueous solvent and a lithium salt dissolved in the non-aqueous solvent.

[0108] Examples of non-aqueous solvents are cyclic carbonate solvents, chain carbonate solvents, cyclic ether solvents, chain ether solvents, cyclic ester solvents, chain ester solvents or fluorinated solvents. Examples of cyclic carbonate solvents are ethylene carbonate, propylene carbonate or butylene carbonate. Examples of chain carbonate solvents are dimethyl carbonate, ethyl methyl carbonate or diethyl carbonate. Examples of cyclic ether solvents are tetrahydrofuran, 1,4-dioxane or 1,3-dioxolane. Examples of chain ether solvents are 1,2-dimethoxyethane or 1,2-diethoxyethane. Examples of cyclic ester solvents are γ-butyrolactone. Examples of chain ester solvents are methyl acetate. Examples of fluorinated solvents are fluoroethylene carbonate, methyl fluoropropionate, fluorobenzene, ethyl fluoromethyl carbonate or dimethylene fluorocarbonate. One non-aqueous solvent selected from the above may be used alone. Alternatively, a mixture of two or more non-aqueous solvents selected from the above may be used.

[0109] Examples of lithium salts include LiPF6, LiBF4, LiSbF6, LiAsF6, LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9) or LiC(SO2CF3)3. One lithium salt selected from the above may be used alone. Alternatively, a mixture of two or more lithium salts selected from the above may be used. The concentration of the lithium salt is, for example, 0.5 mol / L or more and 2 mol / L or less.

[0110] As the gel electrolyte, a polymer material impregnated with a non-aqueous electrolyte can be used. Examples of the polymer material are polyethylene oxide, polyacrylonitrile, polyvinylidene fluoride, polymethyl methacrylate, or a polymer having an ethylene oxide bond.

[0111] Examples of cations contained in ionic liquids are:

[0112] (i) aliphatic chain quaternary salts (quaternary salts) such as tetraalkylammonium or tetraalkylphosphonium,

[0113] (ii) an aliphatic cyclic ammonium such as pyrrolidinium, morpholinium, imidazolinium, tetrahydropyrimidinium, piperazinium or piperidinium, or

[0114] (iii) Nitrogen-containing heterocyclic aromatic cations such as pyridinium and imidazolium cations.

[0115] An example of an anion contained in an ionic liquid is PF6 - 、BF4 - 、SbF6 - 、AsF6 - 、SO3CF3 - 、N(SO2CF3)2 - 、N(SO2C2F5)2- 、N(SO2CF3)(SO2C4F9) - or C(SO2CF3)3 - .

[0116] The ionic liquid may contain a lithium salt.

[0117] In order to improve the adhesion between particles, at least one selected from the positive electrode 201, the electrolyte layer 202, and the negative electrode 203 may contain a binder.

[0118] The example of adhesive is polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, aramid resin, polyamide, polyimide, polyamide-imide, polyacrylonitrile, polyacrylic acid, polymethyl acrylate, polyethyl acrylate, polyhexyl acrylate, polymethacrylic acid, polymethyl methacrylate, polyethyl methacrylate, polyhexyl methacrylate, polyvinyl acetate, polyvinyl pyrrolidone, polyether, polyether sulfone, hexafluoropolypropylene, styrene-butadiene rubber or carboxymethyl cellulose. Copolymer can also be used as adhesive. The example of such adhesive is a copolymer of two or more materials selected from tetrafluoroethylene, hexafluoroethylene, hexafluoropropylene, perfluoroalkyl vinyl ether, vinylidene fluoride, chlorotrifluoroethylene, ethylene, propylene, pentafluoropropylene, fluoromethyl vinyl ether, acrylic acid and hexadiene. A mixture selected from two or more of the above materials can also be used as adhesive.

[0119] In order to improve electron conductivity, at least one selected from the positive electrode 201 and the negative electrode 203 may contain a conductive auxiliary agent.

[0120] Examples of conductive additives are:

[0121] (i) Graphites such as natural graphite or artificial graphite,

[0122] (ii) carbon black such as acetylene black or Ketjen black,

[0123] (iii) Conductive fibers such as carbon fibers or metal fibers,

[0124] (iv) fluorinated carbon,

[0125] (v) Metal powders such as aluminum,

[0126] (vi) Conductive whiskers such as zinc oxide and potassium titanate,

[0127] (vii) conductive metal oxides such as titanium oxide, or

[0128] (viii) Conductive polymer compounds such as polyaniline, polypyrrole or polythiophene.

[0129] For cost reduction, the conductive auxiliary agent (i) or (ii) mentioned above may be used.

[0130] Examples of the shape of the battery of the second embodiment include a coin shape, a cylindrical shape, a square shape, a sheet shape, a button shape, a flat shape, or a laminated shape.

[0131] The battery of the second embodiment can be manufactured by the following steps: preparing materials for forming a positive electrode, materials for forming an electrolyte layer, and materials for forming a negative electrode, and using a known method to produce a stacked body in which the positive electrode, the electrolyte layer, and the negative electrode are arranged in this order.

[0132] Example

[0133] Hereinafter, the present disclosure will be described in more detail with reference to Examples and Comparative Examples.

[0134] <Example 1>

[0135] (Production of solid electrolyte materials)

[0136] In an argon atmosphere having a dew point below -60°C (hereinafter referred to as "dry argon atmosphere"), LiCl, LiBr, CaBr2, ZnBr2, YBr3 and GdCl3 are prepared as raw material powders in a molar ratio of LiCl: LiBr: CaBr2: ZnBr2: YBr3: GdCl3 = 1.4: 1.2: 0.18: 0.02: 0.3: 0.7. These raw material powders are crushed and mixed in an agate mortar. The obtained mixture is placed in an alumina crucible and sintered at 500°C for 1 hour in a dry argon atmosphere. The obtained sintered product is crushed in an agate mortar. In this way, a powder of the solid electrolyte material of Example 1 is obtained. The solid electrolyte material of Example 1 has a composition consisting of Li 2.6 Ca 0.18 Zn 0.02 Y 0.3 G 0.7 Br 2.5 Cl 3.5 Represents the composition.

[0137] (Evaluation of ion conductivity)

[0138] Figure 2 A schematic diagram showing a press-forming die 300 for evaluating the ion conductivity of a solid electrolyte material is shown.

[0139] The press forming die 300 includes a punch upper portion 301, a frame die 302, and a punch lower portion 303. The punch upper portion 301 and the punch lower portion 303 are both made of electron conductive stainless steel. The frame die 302 is made of insulating polycarbonate.

[0140] As described below, use Figure 2 The press molding die 300 shown was used to evaluate the ion conductivity of the solid electrolyte material of Example 1.

[0141] In a dry argon atmosphere, the solid electrolyte material powder 101 of Example 1 was filled into the press mold 300. Inside the press mold 300, the punch upper part 301 and the punch lower part 303 applied a pressure of 360 MPa to the solid electrolyte material powder 101 of Example 1.

[0142] Under the state of applying pressure, the punch upper part 301 and the punch lower part 303 are connected to a potentiostat (Princeton Applied Research, VersaSTAT4) equipped with a frequency response analyzer. The punch upper part 301 is connected to the working electrode and the potential measurement terminal. The punch lower part 303 is connected to the counter electrode and the reference electrode. The impedance of the solid electrolyte material is measured by electrochemical impedance measurement at room temperature.

[0143] Figure 3 This is a diagram showing a Cole-Cole diagram obtained by impedance measurement of the solid electrolyte material of Example 1.

[0144] Figure 3 In the example, the real value of the impedance at the measurement point where the absolute value of the phase of the complex impedance is the smallest is regarded as the resistance value of the solid electrolyte material of Example 1 to ion conduction. For this real value, please refer to Figure 3 The arrow R SE Using this resistance value, the ion conductivity was calculated based on the following mathematical formula (2).

[0145] σ=(R SE ×S / t) -1 (2)

[0146] Wherein, σ represents the ion conductivity. S represents the contact area between the solid electrolyte material and the punch upper portion 301 ( Figure 2 is equal to the cross-sectional area of ​​the hollow portion of the frame mold 302). SE represents the resistance value of the solid electrolyte material in the impedance measurement. t represents the thickness of the solid electrolyte material (i.e., Figure 2 , the thickness of the layer formed by the powder 101 of the solid electrolyte material).

[0147] The ion conductivity of the solid electrolyte material of Example 1 measured at 25° C. was 2.49 mS / cm.

[0148] (X-ray diffraction measurement)

[0149] Figure 4This is a diagram showing an X-ray diffraction pattern of the solid electrolyte material of Example 1.

[0150] The X-ray diffraction pattern of the solid electrolyte material of Example 1 was measured using an X-ray diffraction device (Rigaku Corporation, MiniFlex600) in a dry environment with a dew point of -50°C or less by the θ-2θ method. Cu-Kα rays (wavelength as well as ).

[0151] In the X-ray diffraction pattern of the solid electrolyte material of Example 1, there are peaks at 30.25° (i.e., the first peak) and 39.37° (i.e., the second peak). In addition, there are peaks at 15.24° (i.e., the third peak), 16.62° (i.e., the fourth peak), and 47.05° (i.e., the fifth peak). Therefore, the solid electrolyte material of the first embodiment contains the first crystal phase (i.e., trigonal crystal).

[0152] (Battery production)

[0153] In a dry argon atmosphere, the solid electrolyte material of Example 1 and LiCoO 2 were prepared in a volume ratio of 30:70. These materials were mixed in a mortar to obtain a mixture.

[0154] The solid electrolyte material (80 mg) of Example 1 and the above mixture (10 mg) were sequentially stacked in an insulating cylinder having an inner diameter of 9.5 mm. A pressure of 720 MPa was applied to the obtained stack to form a solid electrolyte layer and a first electrode. The solid electrolyte layer had a thickness of 400 μm.

[0155] Next, metal In (thickness: 200 μm), metal Li (thickness: 200 μm), and metal In (thickness: 200 μm) were stacked in this order on the solid electrolyte layer. A pressure of 80 MPa was applied to the obtained stacked body to form a second electrode.

[0156] Next, a current collector made of stainless steel was attached to the first electrode and the second electrode, and a current collecting lead was attached to the current collector.

[0157] Finally, an insulating ferrule was used to block the inside of the insulating tube from the outside atmosphere, thereby sealing the inside of the tube. In this manner, the battery of Example 1 was obtained.

[0158] (Charge and discharge test)

[0159] Figure 6 : is a graph showing the initial discharge characteristics of the battery of Example 1. The initial discharge characteristics were measured in the following manner.

[0160] The battery of Example 1 was placed in a constant temperature chamber at 25°C.

[0161] At 76μA / cm 2 The battery of Example 1 was charged at a current density of 1.50 V until a voltage of 3.68 V was reached. This current density is equivalent to a 0.05C rate (multiplication rate).

[0162] Next, at 76 μA / cm 2 The battery of Example 1 was discharged at a current density of 1.88V until a voltage of 1.88V was reached.

[0163] As a result of the charge and discharge test, the battery of Example 1 had an initial discharge capacity of 0.73 mAh.

[0164] <Examples 2 to 37>

[0165] (Production of solid electrolyte materials)

[0166] The solid electrolyte materials of Examples 2 to 37 were obtained in the same manner as in Example 1 except for the types and molar ratios of the raw material powders. The types and molar ratios of the raw material powders are shown in Table 1.

[0167] The compositions of the solid electrolyte materials of Examples 2 to 37 are shown in Table 2. Table 2 shows the values ​​corresponding to a, b, x, y, and z of the composition formula (1), and the element types of M1 and M2.

[0168] (Evaluation of ion conductivity)

[0169] The ion conductivity of the solid electrolyte materials of Examples 2 to 37 was measured in the same manner as in Example 1. Table 2 shows the measurement results.

[0170] (X-ray diffraction measurement)

[0171] The X-ray diffraction patterns of the solid electrolyte materials of Examples 2 to 37 were measured in the same manner as in Example 1.

[0172] Figure 4 : is a figure which shows the X-ray diffraction pattern of the solid electrolyte material of Examples 1 to 18. Figure 5 3 is a diagram showing the X-ray diffraction patterns of the solid electrolyte materials of Examples 19 to 37. The angles of the observed X-ray diffraction peaks are shown in Table 3. Figure 4 as well as Figure 5 As shown, the solid electrolyte materials of Examples 1 to 37 all contain the first crystal phase.

[0173] (Charge and discharge test)

[0174] Using the solid electrolyte materials of Examples 2 to 37, the same operation as in Example 1 was performed to obtain batteries of Examples 2 to 37. Using the batteries of Examples 2 to 37, a charge and discharge test was performed in the same manner as in Example 1. As a result, the batteries of Examples 2 to 37 were charged and discharged well in the same manner as in Example 1.

[0175] <Comparative Examples 1 and 2>

[0176] (Production of solid electrolyte materials)

[0177] The solid electrolyte materials of Comparative Examples 1 and 2 were obtained in the same manner as in Example 1 except for the types and molar ratios of the raw material powders. Table 1 shows the types and molar ratios of the raw material powders.

[0178] The compositions of the solid electrolyte materials of Comparative Examples 1 and 2 are shown in Table 2. Table 2 shows the values ​​corresponding to a, b, x, y, and z in the composition formula (1), and the element types of M1 and M2.

[0179] (Evaluation of ion conductivity)

[0180] The ion conductivity of the solid electrolyte materials of Comparative Examples 1 and 2 was measured in the same manner as in Example 1. Table 2 shows the measurement results.

[0181] Table 1

[0182]

[0183] Table 2

[0184]

[0185] Table 3

[0186]

[0187] <Inspection>

[0188] The solid electrolyte materials of Examples 1 to 37 have high lithium ion conductivity of 1 mS / cm or more at around room temperature.

[0189] Comparison of Examples 1 to 37 with Comparative Examples 1 and 2 shows that when the solid electrolyte material is composed of Li, M1, M2, and X, M1 is at least two selected from Ca, Mg, and Zn, M2 is at least one selected from Y, Gd, and Sm, and X is at least one selected from F, Cl, Br, and I, the solid electrolyte material has higher ion conductivity than when it is not composed as described above. This is believed to be because a path for lithium ion diffusion is easily formed.

[0190] It can be seen from Examples 1 to 16 and 31 to 37 that the solid electrolyte material has high ion conductivity when M1 is Ca and Zn. This is considered to be because a path for lithium ion diffusion is easily formed.

[0191] If the value of a in the composition formula (1) is greater than 0 and not greater than 0.3, the solid electrolyte material has high ion conductivity. This is considered to be because a path for lithium ion diffusion is easily formed.

[0192] If the value of b in the composition formula (1) is 0 or more and 0.1 or less, the solid electrolyte material has high ion conductivity. This is considered to be because a path for lithium ion diffusion is easily formed.

[0193] If the value of x in the composition formula (1) is greater than 0 and not more than 0.5, the solid electrolyte material has high ion conductivity. This is considered to be because a path for lithium ion diffusion is easily formed.

[0194] When the value of y in the composition formula (1) is 0 or more and 0.9 or less, the solid electrolyte material has high ion conductivity. This is considered to be because a path for lithium ion diffusion is easily formed.

[0195] It can be seen from Examples 17 to 30 that when M1 is Ca and Mg, the solid electrolyte material has high ion conductivity.

[0196] In addition, if the value of z in the composition formula (1) is 3 or more and 4.5 or less, the solid electrolyte material has high ion conductivity. This is considered to be because a path for lithium ion diffusion is easily formed.

[0197] Depend on Figure 4 as well as Figure 5 It is known that the solid electrolyte material has high ion conductivity when the first peak, the second peak, the third peak, the fourth peak, and the fifth peak are present in the X-ray diffraction patterns of the solid electrolyte materials of Examples 1 to 37. This is considered to be because it is easier to form a path for lithium ion diffusion.

[0198] In all of Examples 1 to 37, the batteries were charged and discharged at room temperature.

[0199] Since the solid electrolyte materials of Examples 1 to 37 do not contain sulfur, they do not generate hydrogen sulfide.

[0200] As described above, the solid electrolyte material of the present disclosure has high lithium ion conductivity and provides a battery that can be well charged and discharged, and is therefore suitable.

[0201] Industrial Applicability

[0202] The solid electrolyte material disclosed herein can be used in, for example, an all-solid lithium-ion secondary battery.

[0203] Explanation of symbols

[0204] 100 Solid Electrolyte Particles

[0205] 101 Powder of solid electrolyte material

[0206] 201 Positive electrode

[0207] 202 electrolyte layer

[0208] 203 Negative electrode

[0209] 204 Positive electrode active material particles

[0210] 205 Negative electrode active material particles

[0211] 300 Pressurized forming die

[0212] 301 Punch upper part

[0213] 302 frame mold

[0214] 303 punch lower part

[0215] 1000 Batteries

Claims

1. A solid electrolyte material, which is formed by Li, M1, M2 and X, in, M1 is at least two selected from Ca, Mg and Zn, M2 is at least one selected from Y, Gd and Sm, X is at least one selected from F, Cl, Br and I, The solid electrolyte material is represented by the following composition formula (1): <h2 style=";text-align:left;direction:ltr">Li<h2 style=";text-align:left;direction:ltr"> 3-2a-3b <h2 style=";text-align:left;direction:ltr"> (Ca<h2 style=";text-align:left;direction:ltr"> 1-x <h2 style=";text-align:left;direction:ltr"> M1′<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> )<h2 style=";text-align:left;direction:ltr"> a <h2 style=";text-align:left;direction:ltr"> (Y<h2 style=";text-align:left;direction:ltr"> 1-y <h2 style=";text-align:left;direction:ltr"> M2′<h2 style=";text-align:left;direction:ltr"> y <h2 style=";text-align:left;direction:ltr"> )<h2 style=";text-align:left;direction:ltr"> 1+b <h2 style=";text-align:left;direction:ltr"> Br<h2 style=";text-align:left;direction:ltr"> 6-z <h2 style=";text-align:left;direction:ltr"> Cl<h2 style=";text-align:left;direction:ltr"> z <h2 style=";text-align:left;direction:ltr"> (1) in, M1′ is at least one selected from Zn and Mg, M2′ is at least one selected from Gd and Sm, And satisfy the following 4 mathematical formulas: 0<a≤0.3、 0≤b≤0.1、 0<x≤0.5、 0≤y≤0.9 and 0≤z≤6。 2. The solid electrolyte material according to claim 1, wherein M1 is Ca and Mg, or Ca and Zn.

3. The solid electrolyte material according to claim 1 or 2, wherein X is at least one selected from Cl and Br.

4. A solid electrolyte material, which is formed by Li, M1, M2 and X, in, M1 is at least two selected from Ca, Mg and Zn, M2 is at least one selected from Y, Gd and Sm, X is at least one selected from F, Cl, Br and I, In an X-ray diffraction pattern obtained by X-ray diffraction measurement of the solid electrolyte material using Cu-Kα rays, a first peak exists within a range of a diffraction angle 2θ of 30.0° or more and 31.0° or less, and The second peak exists in the range of the diffraction angle 2θ of 39.0° to 40.3°.

5. The solid electrolyte material according to claim 4, wherein in an X-ray diffraction pattern obtained by X-ray diffraction measurement of the solid electrolyte material using Cu-Kα rays, a third peak exists within a range of a diffraction angle 2θ of 15.0° or more and 15.7° or less, There is a fourth peak in the range of diffraction angle 2θ of 16.3° or more and 17.1° or less, and The fifth peak exists in the range of the diffraction angle 2θ of 46.6° to 48.1°.

6. The solid electrolyte material according to claim 4 or 5, wherein M1 is Ca and Mg, or Ca and Zn.

7. The solid electrolyte material according to claim 4 or 5, wherein X is at least one selected from Cl and Br.

8. The solid electrolyte material according to claim 4 or 5, which is represented by the following composition formula (1): <h2 style=";text-align:left;direction:ltr">Li<h2 style=";text-align:left;direction:ltr"> 3-2a-3b <h2 style=";text-align:left;direction:ltr"> (Ca<h2 style=";text-align:left;direction:ltr"> 1-x <h2 style=";text-align:left;direction:ltr"> M1′<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> )<h2 style=";text-align:left;direction:ltr"> a <h2 style=";text-align:left;direction:ltr"> (Y<h2 style=";text-align:left;direction:ltr"> 1-y <h2 style=";text-align:left;direction:ltr"> M2′<h2 style=";text-align:left;direction:ltr"> y <h2 style=";text-align:left;direction:ltr"> )<h2 style=";text-align:left;direction:ltr"> 1+b <h2 style=";text-align:left;direction:ltr"> Br<h2 style=";text-align:left;direction:ltr"> 6-z <h2 style=";text-align:left;direction:ltr"> Cl<h2 style=";text-align:left;direction:ltr"> z <h2 style=";text-align:left;direction:ltr"> (1) in, M1′ is at least one selected from Zn and Mg, M2′ is at least one selected from Gd and Sm, And satisfy the following 4 mathematical formulas: 0<a≤0.3、 0≤b≤0.1、 0<x≤0.5、 0≤y≤0.9 and 0≤z≤6。 9. A battery comprising: positive electrode; a negative electrode; and An electrolyte layer is provided between the positive electrode and the negative electrode, At least one selected from the positive electrode, the negative electrode, and the electrolyte layer contains the solid electrolyte material according to any one of claims 1 to 8.